Mekanisme Event Fansign melalui Transaksi Jual Beli Album K-Pop di Aplikasi Weverse Perspektif Hukum Ekonomi Syariah - Latifah Azkia; Sofia Ridha (AHKAM, 2026)
The practice of K-Pop fansign events that require the purchase of physical albums through the Weverse application as a prerequisite for participation in a lottery to meet idols raises legal questions regarding their validity from the perspective of Islamic economic law, particularly concerning the potential element of maisir (gambling) in their mechanism. This study aimed to analyze the mechanism of fansign events conducted through the sale and purchase of K-Pop albums on the Weverse application and to examine their compliance with the principles of Islamic economic law. A library research method with a descriptive qualitative approach was employed, using data obtained from Islamic economic law literature, scholarly journals, books, and official information on the Weverse application, which were then analyzed qualitatively using an inductive approach. The results show that the mechanism of fansign events on Weverse begins with the purchase of physical albums, followed by registration for the fansign lottery and a random drawing to determine the winners, thus, from a fiqh perspective, involving a multi-contract system, namely a salam sale contract for the album and a hibah contract in the form of an opportunity to participate in the fansign lottery. From the perspective of Islamic economic law, this practice may be deemed permissible as long as the purchase of the album is based on the need and intention to own the album, not solely to participate in the lottery, and is not carried out excessively in a way that approximates maisir. The implications of this study provide a normative reference for the development of digital transaction practices that are aligned with sharia principles, particularly in designing promotional schemes and events that avoid elements of gharar and maisir.